77 PREDICTORS OF IN-STENT RESTENOSIS AND PATIENT OUTCOME AFTER PERCUTANEOUS CORONARY INTERVENTION IN DIABETES MELLITUS. Issue 1 (1st January 2007) - Sukhija, R.; Aleti, S.; Sureddi, R.; Molavi, B.; Sachdeva, R.; Sinha, A.; Mehta, J. L.
Abstract : Background: Diabetics have a significantly higher incidence of major adverse cardiac events (MACE) and in-stent restenosis (ISR) than nondiabetics after percutaneous coronary intervention (PCI). Predictors of MACE and ISR are uncertain in diabetics. There are few data about the association of microalbuminuria and diabetic retinopathy with MACE and ISR. Methods: We studied 195 patients (63 ± 9 years, 98% males) with diabetes mellitus who underwent PCI. We investigated ISR and incidence of MACE (cumulative of myocardial infarction, revascularization, and deaths from cardiac causes) in these patients; all patients were on statins. Results: Of 195 patients, 107 had follow-up catheterization at a mean of 16 months. Of these 107 patients, 56 developed ISR. In the multivariate model, microalbuminuria or diabetic retinopathy did not have any significant association with ISR (OR = 0.659, CI 0.247-1.75, p = .40 and OR = 2.02, CI 0.64-6.37, p = .22, respectively) or MACE (OR = 1.342, CI 0.7-2.55, p = .37 and OR = 0.945, CI 0.437-2.04, p = .88, respectively). Plasma level of HDL cholesterol was inversely associated with the incidence of ISR (OR −0.928, CI 0.876-0.983, p = .011) and MACE (OR −0.965, CI 0.931-1, p = .048). Use of a Cypher stent (vs bare metal stent) had a negative association with ISR (OR −0.171, CI 0.05-0.585, p = .004). The presence of renal disease was associated with higher MACE (OR 3.19, CI 1.45-7.031, p = .0039). The multivariate model was adjusted for the size of the target vessel, complexity of lesion, type of stent, and plasma LDL levels. Conclusion: HDL cholesterol level is inversely associated with ISR and MACE after PCI in high-risk diabetic patients. However, microalbuminuria or diabetic retinopathy are not associated with ISR or MACE.